1 - Continuity and Change in Students’Account of Race and Class Relations at a South African University - Deevia Bhana, (Journal of Higher Education in Africa, 2013)
This article draws from an interview-based study of students at the University of KwaZulu-Natal highlighting the ways in which they give meaning to race. Racist practices at universities in South Africa have received widespread condemnation and universities are at the forefront in confronting and dealing with the persistence of racism. In this context, the article seeks to develop an understanding of the contextually specific ways through which race is given content and the possibilities that they may present for change. The data shows that the specific configurations of race as described by African and Indian students at the university where the study was conducted suggest constrictions and continuities of separateness as they demonstrate change. Rejecting an analysis that is based on fixed meanings of race, the article theorises that race is complicated by broader social structures, and class remains an important variable in race relations. Race continues to be salient in the everyday lives of students but race and student life must be understood through class. The article analyses further the ways in which students point to possibilities to enhance change working creatively within the university to bring about racial mixing. The article concludes with some recommendations for change.